Productivity potential and profitability of castor (Ricinus communis L.) with sprinkler irrigation: PRODUCTIVITY POTENTIAL AND PROFITABILITY OF CASTOR WITH SPRINKLER IRRIGATION - M PADMAIAH; G D S KUMAR (Journal of Oilseeds Research, 2014)
In Andhra Pradesh, Amrabad Mandal in Mahabubnagar district was inhabited predominantly by Chenchus. They depend on forest produce for their livelihood. The area under castor gradually came down in these villages due to erratic rains and inadequate irrigation. Farmers felt the need for an efficient water management system for castor. Castor crop was re-introduced in to these villages with sprinkler irrigation with Tribal Sub Plan. The productivity potential and profitability of castor increased with sprinkler system as compared to flood irrigation. The factors for ready adoption of sprinklers were delineated such as limited availability of water, controlling of irrigation depth increased crop yield and converting rainfed area to irrigated area. Adoption of sprinkler irrigation have changed the economic dependence on money lenders, improved the input use in castor and increased the gross monetary returns to the Chenchu farmers.